2010
DOI: 10.1111/j.1365-2966.2010.16661.x
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of star formation at large galactic radii

Abstract: We have compared far‐ultraviolet (FUV), near‐ultraviolet (NUV) and Hα measurements for star‐forming regions in 21 galaxies, in order to characterize the properties of their discs at radii beyond the main optical radius (R25). In our representative sample of extended and non‐extended ultraviolet (UV) discs, we find that half of the extended UV discs also exhibit extended Hα emission. We find that extended UV discs fall into two categories: those with a sharp truncation in the Hα disc close to the optical edge (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 70 publications
6
89
0
Order By: Relevance
“…The slope of the outer disk profile is similar to that determined with an isophote fitting routine, which is expected because the ellipse parameters were chosen at an outer disk isophote. density profile (Crosthwaite et al 2002), the gas velocity field (Rogstad et al 1974, and see Figure 1(f)), and the ionized gas surface density (Martin & Kennicutt 2001;Goddard et al 2010). While the latter of these observations might have pointed to a significant decline in the SFR surface density at this radius, FUV observations show a smooth decline implying that star formation has indeed occurred throughout the outer disk.…”
Section: The Nir Surface Brightness Profilementioning
confidence: 86%
See 1 more Smart Citation
“…The slope of the outer disk profile is similar to that determined with an isophote fitting routine, which is expected because the ellipse parameters were chosen at an outer disk isophote. density profile (Crosthwaite et al 2002), the gas velocity field (Rogstad et al 1974, and see Figure 1(f)), and the ionized gas surface density (Martin & Kennicutt 2001;Goddard et al 2010). While the latter of these observations might have pointed to a significant decline in the SFR surface density at this radius, FUV observations show a smooth decline implying that star formation has indeed occurred throughout the outer disk.…”
Section: The Nir Surface Brightness Profilementioning
confidence: 86%
“…While the latter of these observations might have pointed to a significant decline in the SFR surface density at this radius, FUV observations show a smooth decline implying that star formation has indeed occurred throughout the outer disk. Rather, Goddard et al (2010) have found the ages of star forming regions in the outer disk are typically old enough that the most massive, ionizing stars may have died, thus causing the discrepancy between the Hα and FUV profiles. Therefore, it seems that the outer disk portion of M83 shows signatures of recent gas accretion and star formation that have begun building , and H i (bottom) surface brightness profiles, tracing the total stellar surface density, the recent star formation, and the gas reservoir, respectively.…”
Section: The Nir Surface Brightness Profilementioning
confidence: 99%
“…Four well-known XUV disks have been shown to have discontinuities between their inner and outer disk abundance profiles and an approximately constant abundance profile in the outer disk with values between approximately 0.2 and 0.33 Z (Bresolin et al 2009(Bresolin et al , 2012Gil de Paz et al 2007b;Goddard et al 2010). While the existing gas can be enriched to this level by constant star formation over a period of a few Gyr, the low stellar content in the outer disk appears inconsistent with that level of star formation for an extended time.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the universal IMF looks very attractive, because there are no direct evidences that in normal (not star bursting) galaxies IMF is different even for peripheral regions (Goddard et al 2010;Koda et al 2012). Nevertheless a comparison of IMF of individual young stellar clusters demonstrate that significant IMF variations are real (Dib 2014).…”
Section: Top-light Imfmentioning
confidence: 99%
“…Another example give LSB galaxies where a steep IMF may explain the combination of metallicity and color indices (Lee et al 2004). The different behaviour of UV and H α radial profiles of spiral galaxies also suggests the variation of IMF along radius (Boissier et al 2007;Krumholz & McKee 2008;Meurer et al 2009), although it also may be explained for the standart IMF (Goddard et al 2010). …”
Section: Top-light Imfmentioning
confidence: 99%